Does criticisms overcome the praises of Journal Impact Factor? - Fooladi, M.; Salehi, H.; Yunus, M.M.; Farhadi, M.; Aghaei Chadegani, A.; Farhadi, H.; Ale Ebrahim, N. (Canadian Center of Science and Education, 2013)
Journal impact factor (IF) as a gauge of influence and impact of a particular journal comparing with other journals in the same area of research, reports the mean number of citations to the published articles in particular journal. Although, IF attracts more attention and being used more frequently than other measures, it has been subjected to criticisms, which overcome the advantages of IF. Critically, extensive use of IF may result in destroying editorial and researchers' behaviour, which could compromise the quality of scientific articles. Therefore, it is the time of the timeliness and importance of a new invention of journal ranking techniques beyond the journal impact factor.